2012
DOI: 10.1590/s0004-27492012000400011
|View full text |Cite
|
Sign up to set email alerts
|

Intravitreal ranibizumab and bevacizumab therapy for choroidal neovascularization in age-related macular degeneration with extensive pre-existing geographic atrophy

Abstract: Purpose: To report the response of choroidal neovascularization to intravitreal ranibizumab or bevacizumab treatment in the setting of age-related macular degeneration with extensive pre-existing geographic atrophy of the retinal pigment epithelium. Methods: This is a retrospective case series of 11 eyes in ten consecutive patients retrieved from a photographic database. The patients were treated with ranibizumab or bevacizumab for neovascular age-related macular degeneration with pre-exis ting geographic atro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
3
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 16 publications
1
3
0
1
Order By: Relevance
“…Eight of our 10 patients improved their vision with ranibizumab treatment for CNV in AMD with extensive pre-existing GA and reports of ranibizumab treatment of choroidal neovascularization in the setting of pre-existing Geographic Atrophy from AMD (24,25) with similar results as: good anatomic response with disappearance of the subretinal fluid, improved visual acuity and stabilized final visual results consistent with others ranibizumab studies (11,12,24,25) . …”
Section: Resultssupporting
confidence: 85%
“…Eight of our 10 patients improved their vision with ranibizumab treatment for CNV in AMD with extensive pre-existing GA and reports of ranibizumab treatment of choroidal neovascularization in the setting of pre-existing Geographic Atrophy from AMD (24,25) with similar results as: good anatomic response with disappearance of the subretinal fluid, improved visual acuity and stabilized final visual results consistent with others ranibizumab studies (11,12,24,25) . …”
Section: Resultssupporting
confidence: 85%
“…Favorable anatomical and visual function outcomes were found after treatment with either ranibizumab or bevacizumab. However, Amaro et al mentioned that the improvement in visual acuity in their study was not as remarkable as in other anti-VEGF trials, incriminating underlying GA [62]. Querques et al found that treatment of CNV with ranibizumab in eyes with concomitant GA resulted in significant reduction of the morphological manifestations of CNV at 24 months of treatment in 21 naïve eyes; however, visual acuity deteriorated, perhaps because the underlying GA prevented any favorable outcome in visual function [63].…”
Section: The Combined Ga/cnv Phenotype Of Amdmentioning
confidence: 80%
“…Currently, there are 3 medications in widespread use: bevacizumab (Avastin; Genentech, Inc., South San Francisco, CA), ranubizumab (Lucentis; Genentech, Inc., South San Francisco, CA), and aflibercept (Eyelea; Regeneron, Inc., Tarrytown, NY). Anti-VEGF injections were recently studied for their efficacy in treating CNV with underlying GA. Amaro et al studied the effect of anti-VEGF treatment on the combined GA/CNV phenotype in a case series of 11 eyes [62]. Favorable anatomical and visual function outcomes were found after treatment with either ranibizumab or bevacizumab.…”
Section: The Combined Ga/cnv Phenotype Of Amdmentioning
confidence: 99%
“…Excessive amounts of vascular endothelial growth factor (VEGF) is a major pathological change in wet AMD, and anti-VEGF can relieve or delay the progress of wet AMD (Xu et al, 2015; Wang et al, 2016). Anti-VEGF treatment of the combined dry/wet AMD phenotype was reported to be effective in a case series of 11 eyes (Amaro and Roller, 2012). In the present study, we found that VEGF-positive spots were located mainly in the inner retinal layers from the NFL to the IPL and in the RPE in young mice, but they were more widely distributed in the INL, OPL, and ONL in aged mice and less so in the RPE in aged WT-21 m/Veh and 3xTg-21 m/Veh mice (Supplementary Figure S6).…”
Section: Resultsmentioning
confidence: 99%